Adoption of Mobile Apps: The Role of Experience - Mahardika, Harryadin (UI Scholars Hub, 2021)
The form of initial experience with mobile application determines consumers’ likelihood to adopt it. This paper examines the effects of two forms of experience (direct versus indirect) toward the formation of consumers behavioral intentions (versus behavioral expectations) to adopt mobile applications. A direct experience induces concrete mental process that underlies the formation of behavioral expectations, whereas an indirect experience induces abstract mental process that underlies the formation of behavioral intentions. Results from Experiment 1 show significant increase in behavioral expectations’ predictive ability when subjects engaged in a direct experience than an indirect experience. Meanwhile, the effects of a direct experience were subtle toward behavioral intentions’ predictive ability. In Experiment 2, the intensity of direct experience revealed additional caveats on the predictive ability of behavioral intentions and behavioral expectations. It is found that higher intensity of a direct experience has a stronger effect toward behavioral expectations than behavioral intentions. Findings of these experiments could be used as a ground to design an intervention strategy for mobile applications pre-adoption experience.